Signs of neuroaxonal injury in preeclampsia-A case control study. - Malin Andersson; Jonatan Oras; Sven Egron Thörn; Ove Karlsson; Peter Kälebo; Henrik Zetterberg; Kaj Blennow; Lina Bergman (PLoS ONE)
Background Cerebral injury is a common cause of maternal mortality due to preeclampsia and is challenging to predict and diagnose. In addition, there are associations between previous preeclampsia and stroke, dementia and epilepsy later in life. The cerebral biomarkers S100B, neuron specific enolase, (NSE), tau protein and neurofilament light chain (NfL) have proven useful as predictors and diagnostic tools in other neurological disorders. This case-control study sought to determine whether cerebral biomarkers were increased in cerebrospinal fluid (CSF) as a marker of cerebral origin and potential cerebral injury in preeclampsia and if concentrations in CSF correlated to concentrations in plasma. Methods CSF and blood at delivery from 15 women with preeclampsia and 15 women with normal pregnancies were analysed for the cerebral biomarkers S100B, NSE, tau protein and NfL by Simoa and ELISA based methods. MRI brain was performed after delivery and for women with preeclampsia also at six months postpartum. Results Women with preeclampsia demonstrated increased CSF- and plasma concentrations of NfL and these concentrations correlated to each other. CSF concentrations of NSE and tau were decreased in preeclampsia and there were no differences in plasma concentrations of NSE and tau between groups. For S100B, serum concentrations in preeclampsia were increased but there was no difference in CSF concentrations of S100B between women with preeclampsia and normal pregnancy. Conclusion NfL emerges as a promising circulating cerebral biomarker in preeclampsia and increased CSF concentrations point to a neuroaxonal injury in preeclampsia, even in the absence of clinically evident neurological complications.